Identification of FCER1G as a cyclosporin A plus corticosteroid sensitization gene in female patients with Vogt-Koyanagi-Harada disease - Chang, Rui (Clinical immunology (Orlando, Fla.), 2023)
Copyright © 2023 Elsevier Inc. All rights reserved.